2018
DOI: 10.1177/1078155217752075
|View full text |Cite
|
Sign up to set email alerts
|

The value of fixed rasburicase dosing versus weight-based dosing in the treatment and prevention of tumor lysis syndrome

Abstract: Background Rasburicase is a recombinant urate oxidase enzyme used for the treatment and prevention of tumor lysis syndrome. Our objective was to assess the efficacy of indication-based, low-dose rasburicase administration compared to the Food and Drug Administration-approved weight-based dosing. Methods This was a retrospective cohort study utilizing data from a tertiary medical center including patients admitted from 2012 to 2016, who received at least one dose of rasburicase. The primary outcome was achievin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Multiple retrospective chart reviews and meta-analyses have demonstrated the clinical and financial effectiveness of single fixed-dose rasburicase in the treatment and prevention of hyperuricemia or TLS in tertiary academic centers. 24,916 Our study is the first, to our knowledge, to publish real word data of rasburicase utilization and the efficacy of single fixed doses (3 or 6 mg) within a large network of community oncology practices. American Society of Clinical Oncology (ASCO) guidelines recommend rasburicase for patients with intermediate risk of TLS if hyperuricemia develops, and National Comprehensive Cancer Network (NCCN) guidelines for B-cell lymphomas recommend to consider TLS prophylaxis for Burkitt’s lymphoma, lymphoblastic lymphoma, and occasionally diffuse large b-cell lymphoma (DLBCL).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple retrospective chart reviews and meta-analyses have demonstrated the clinical and financial effectiveness of single fixed-dose rasburicase in the treatment and prevention of hyperuricemia or TLS in tertiary academic centers. 24,916 Our study is the first, to our knowledge, to publish real word data of rasburicase utilization and the efficacy of single fixed doses (3 or 6 mg) within a large network of community oncology practices. American Society of Clinical Oncology (ASCO) guidelines recommend rasburicase for patients with intermediate risk of TLS if hyperuricemia develops, and National Comprehensive Cancer Network (NCCN) guidelines for B-cell lymphomas recommend to consider TLS prophylaxis for Burkitt’s lymphoma, lymphoblastic lymphoma, and occasionally diffuse large b-cell lymphoma (DLBCL).…”
Section: Discussionmentioning
confidence: 99%
“…It is approved for treatment of tumour lysis syndrome as a weight-based dose daily for 5 days, 9 although single and fixed-dose regimens have been reported to be effective in lowering uric acid levels. 10,11 Allopurinol, available in both enteral and parenteral forms, is an inhibitor of xanthine oxidase, which blocks further synthesis of uric acid from urate. However, allopurinol does not affect existing serum uric acid levels and thus may require a longer treatment course.…”
mentioning
confidence: 99%